Hypocholesterolaemic effect of rat-administered oral doses of the isolated 7S globulins from cowpeas and adzuki beans - Ederlan S. Ferreira; Ana Lucia S. Amaral; Aureluce Demonte; Cleslei F. Zanelli; Jessica Capraro; Marcello Duranti; Valdir A. Neves (Journal of Nutritional Science, 2015)
The role of seed proteins, especially soyabean 7S globulins, in controlling dyslipidaemia is widely acknowledged. Amino acid sequence homology among the proteins of this family could reflect similar biological functions in other species. The aim of the present study was to unveil a hypolipidaemic effect of the 7S globulins from cowpeas (7S-C) and adzuki beans (7S-A), administered orally to rats fed a hypercholesterolaemic (HC; high cholesterol and TAG) diet for 28 d. A total of forty-five rats were divided into five groups (nine rats per group): (1) standard (STD) diet; (2) HC diet; (3) HC diet + 7S-C (300 mg/kg per d); (4) HC diet + 7S-A (300 mg/kg per d); and (5) HC diet + simvastatin (SVT; 50 mg/kg per d), as a control. Significant decreases in food intake and final body weight of rats receiving HC + 7S-C and HC + 7S-A diets compared with groups fed the HC and STD diets were observed. Significant decreases in serum total and non-HDL-cholesterol of 7S-C, 7S-A and SVT groups were also observed. HDL-cholesterol levels increased in the 7S-C, 7S-A and SVT groups, while hepatic cholesterol and TAG concentrations were significantly lower than in the HC diet group for the 7S-C-supplemented group only. Faecal excretions of fat and cholesterol in HC diet groups were considerably higher in animals consuming the 7S globulins. The results show that cowpea and adzuki bean 7S globulins promote cholesterol-decreasing effects in hypercholesterolaemic rats even at low dosages, as already observed for other legume seed storage proteins of this family. This main effect is discussed in relation to the possible mechanisms of action.